Improvement effects of treating with calcined oyster shell and carbonized cow dung compost on clay with high water content - Zichen Zhang; Kiyoshi Omine; Cui Li; Shenjie Shi; Flemmy Samuel Oye (Case Studies in Construction Materials, 2022)
Effective waste treatment as a new binder apply to improve soft clay is an economical and environmental solution for stabilizing soft clay. In this context, this study proposes a high-water content clay improvement case using calcined waste oyster shells (COS) and carbonized cow dung compost (CC) as substitutes for cement to stabilize clay with high-water content. In this study, the solidifying agent/water ratio, C/(w/100), was introduced as an important parameter to evaluate the improvement effect of COS stabilized clay. Compared with ordinary Portland cement (OPC), the mixed amount of COS required for effective improvement is significantly reduced (≈43–46 %). In addition, the incorporation of more environmentally friendly carbonation materials improves the improvement effect of COS stabilized clay. A comparison with commercial wood charcoal proved that CC with better adsorption capacity significantly improved high-water-content clay. The test results of energy-dispersive X-ray spectrometry (EDS) and scanning electron microscope (SEM) show that with an increase in COS content, the reaction product hydrated calcium silicate is formed, and the improvement effect of stabilized clay is enhanced. In addition, the incorporation of water-absorbent materials reduced the void space in the clay structure, which is conducive to stabilizing the internal cementation of clay. SEM evidenced the change of microstructure of the stabilized clay owing to the gel materials.